An analysis of secular trends in method-specific suicides in Japan, 1950–1975 - Eiji Yoshioka; Yasuaki Saijo; Ichiro Kawachi (Population Health Metrics, 2017)
Abstract Background In Japan, a dramatic rise in suicide rates was observed in the 1950s, especially among the younger population, and then the rate decreased rapidly again in the 1960s. The aim of this study was to assess secular trends in method-specific suicides by gender and age in Japan between 1950 and 1975. We paid special attention to suicides by poisoning (solid and liquid substances), and their contribution to dramatic swings in the overall suicide rate in Japan during the 1950s and 1960s. Methods Mortality and population data were obtained from the Vital Statistics of Japan and Statistics Bureau, Ministry of Internal Affairs and Communications in Japan, respectively. We calculated method-specific age-standardized suicide rates by gender and age group (15–29, 30–49, or 50+ years). Results The change in the suicide rate during the research period was larger in males than females in all age groups, and was more marked among people aged 15–29 years compared to those aged 30–49 years and 50 years or over. Poisoning by solid and liquid substances overwhelmingly contributed to the dramatic change in the overall suicide rates in males and females aged 15–49 years in the 1950s and 1960s. For the peak years of the rise in poisoning suicides, bromide was the most frequently used substance. Conclusions Our results for the 1950s and 1960s in Japan illustrated how assessing secular trends in method-specific suicides by gender and age could provide a deeper understanding of the dramatic swings in overall suicide rate. Although rapid increases or decreases in suicide rates have been also observed in some countries or regions recently, trends in method-specific suicides have not been analyzed because of a lack of data on method-specific suicide in many countries. Our study illustrates how the collection and analysis of method-specific data can contribute to an understanding of dramatic shifts in national suicide rates.